Inclusive Policies and Governance in Banyuwangi Regency - Putri Robiatul Adawiyah; Juariyah (POLITICO, 2025)
This study examines inclusive policies and governance in Banyuwangi Regency, focusing on the interaction between policy actors and sectors within an inclusive governance framework. The study analyzes the roles of key stakeholders, including the local government, legislative institutions, social services, civil society organizations, private sector, media, and community groups in shaping and implementing inclusive policies. The findings show that inclusive governance in Banyuwangi is strengthened by the synergy between multi-actor involvement and cross-sectoral integration. Key sectors include public service delivery, policy regulation, education and employment access, disability services, digital innovation, skills development, and participatory assessment mechanisms, that are interconnected and oriented toward addressing the needs of vulnerable and marginalized groups. There is a shift from a charity based approach toward a rights based and empowerment-driven model, supported by collaborative governance mechanisms and adaptive policy innovations. The effectiveness of inclusive governance depends on strong collaboration among stakeholders, alignment across sectors, and the capacity of governance systems to ensure equitable access, participation, and representation for all society.